SEKOLAH ISLAM: ASAL-USUL DAN PERTUMBUHANNYA - Rahman, Aulia; Iswantir, Iswantir (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2023)
This study discusses the origins of Islamic schools in Indonesia. Library research methods. The Islamic school referred to in this study is not an Islamic school in the sense of Islamic Boarding Schools and Madrasahs, but an Islamic school which is better known as the Integrated Islamic School. The presence of an Integrated Islamic School with its integrated curriculum is a new phenomenon in the form of the Islamic education system in Indonesia. Until the late 70s, the Indonesian education system still had a dichotomous pattern. As the Reformation progressed in the 1980s, there were efforts from members of the community to try to get out of the existing system with the idea of an Integrated Islamic School.